CATCH-UP DE ESTATURA NA IDADE ESCOLAR ESTÁ ASSOCIADO COM MASSA ÓSSEA EM ADOLESCENTES? - RODRIGUES, Livia dos Santos (2018)
The objective of the present study was to analyze the effect of catch-up height at school age and bone mineral mass, to identify the socioeconomic and demographic characteristics of the study population, to estimate the prevalence of bone mass below that expected for age in the sample studied and to verify the effect of catch-up height at school age on the bone mineral mass in young adults belonging to the Brazilian cohort of birth of São Luís-MA. It is a prospective study involving three moments of the Consortium of RPS Cohorts in São Luís. In the first article, bone mass at 18-19 years was the outcome variable based on z-score provided through dual energy absorptiometry X-ray (DXA) and the catch-up height, which consists of a z-score change ≥ 0.67, the variable exposure. This association was studied based on a theoretical model constructed using directed acyclic graphs (DAG) and with adjustment for smoking in gestation, sex of the child, gestational age imputed in months, restriction of intrauterine growth, family income in minimum wages , maternal and paternal heights and exclusive breastfeeding until the sixth month. The closest neighbor-type propensity score pairing technique was used. There was no effect of catch-up height at age on adolescent bone mass (Coef = 0.598; 95% CI -0.116 - 1.313; p = 0.101), even after pairing and removing differences from variables studied. In the second article, the variables bone mass of the lumbar spine and total body were as outcomes and the variables of exposure were BMI, length at birth and linear growth and body mass gain in the 1997/98 Cohort of São Luís. a theoretical model with adjustment for maternal schooling in years of study, maternal smoking during gestation, gestational age, sex and family income in minimum wages at school age was used. Conditional growth measures were calculated to avoid the problem of collinearity between the three repeated measures of BMI and height. It was observed after linear regression that the mass gain above the expected in childhood (Coef = 0.149, CI = 0.02 - 0.28, p = 0.023) remained in the lumbar spine, even after adjustment. adolescents (Coef = 0.315, CI = 0.21-0.22, p = 0.001) and linear gain in childhood (Coef = 0.221, CI = 0.10-0.34, p = 0.001). In relation to bone mass of the whole body, mass gain in childhood (Coef = 0.408, CI = 0.28 - 0.54, p = 0.001) and adolescence (Coef = 0.444, CI = 0.33 - (Coef = 0.252, CI = 0.12-0.38, p = <0.001) and adolescence (Coef = 0.210, CI = 0.09-0) , 33, p = 0.001). The findings show that factors related to weight and height growth may be related to bone mass in young people, especially gains in BMI.